Structural equation modeling in epidemiology - Leila Denise Alves Ferreira Amorim; Rosemeire L. Fiaccone; Carlos Antônio S. T. Santos; Tereza Nadya dos Santos; Lia Terezinha L. P. de Moraes; Nelson F. Oliveira; Silvano O. Barbosa; Darci Neves dos Santos; Letícia Marques dos Santos; Sheila M. A. Matos; Maurício L. Barreto (Cadernos de Saúde Pública)
Structural equation modeling (SEM) is an important statistical tool for evaluating complex relations in several research areas. In epidemiology, the use and discussion of SEM have been limited thus far. This article presents basic principles and concepts in SEM, including an application using epidemiological data analysis from a study on the determinants of cognitive development in young children, considering constructs related to organization of the child's home environment, parenting style, and the child's health status. The relations between the constructs and cognitive development were measured. The results showed a positive association between psychosocial stimulus at home and cognitive development in young children. The article presents the contributions by SEM to epidemiology, highlighting the need for an a priori theoretical model for improving the study of epidemiological questions from a new perspective.